(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
competitiveness of the Latvian fisheries sector in the long term depends on thought-out financial management of enterprises and objective and timely identification of various risks. Sound and innovation- and knowledge-based entrepreneurship can contribute to substantial success and growth. The aim of the research is to assess the financial management of micro-enterprises in the Latvian fisheries sector, at the same time providing recommendations for the need in structural reforms and ensuring sustainable financial stability. Based on the chosen assessment methodology, the skills and opportunities of micro-enterprises in creation of capital structure, distribution of financial resources and return were analysed. The information reflected in the framework of the research can assist the institutions, entrepreneurs and researchers involved in establishment and implementation of fisheries policy to better understand the need in successful financial management to ensure a sustainable operation of the sector.